The effect of liquid carbohydrate ingestion on repeated maximal effort exercise in competitive cyclists - Haub, M. D.; Haff, G. G.; Potteiger, J. A. (The Journal of Strength and Conditioning Research, 2003)
We investigated the effects of carbohydrate ingestion during recovery from high-intensity exercise on subsequent high-intensity exercise in trained cyclists. Aerobic power was determined, and the competitive cyclists (N = 7) were familiarized with the 100-kJ test protocol (100KJ-TEST). The subjects performed a first 100KJ-TEST (RIDE-1), ingested 0.7 g·(kg body mass)-1 of Gatorlode (CHO) or placebo (PLC), rested for 60 minutes, and then performed a second 100KJ-TEST (RIDE-2). Blood samples taken before (PRE-1) and after (POST-1) RIDE-1 and before (PRE-2) and after (POST-2) RIDE-2 were analyzed for plasma glucose ([glucose]), lactate, and nonesterified fatty acids ([NEFA]). No significant differences (p > 0.05) were observed between treatments in time to complete RIDE-1 (CHO = 270.3 ± 29.0 seconds; PLC = 269.9 ± 33.0 seconds) and RIDE-2 (CHO = 271.7 ± 26.6 seconds; PLC = 275.3 ± 30.6 seconds). Plasma [glucose] significantly decreased during the 60-minute recovery for PLC. There was an interaction effect for [NEFA] during recovery, with [NEFA] increasing for PLC and decreasing for CHO. Carbohydrate ingestion after maximal exercise does not appear to influence subsequent short-duration maximal effort exercise in competitive cyclists but does alter plasma [glucose] and [NEFA] relative to a PLC condition.